2016
DOI: 10.1074/jbc.m116.713768
|View full text |Cite
|
Sign up to set email alerts
|

Liver MicroRNA-291b-3p Promotes Hepatic Lipogenesis through Negative Regulation of Adenosine 5′-Monophosphate (AMP)-activated Protein Kinase α1

Abstract: In a microarray study, we found that hepatic miR-291b-3p was significantly increased in leptin-receptor-deficient type 2 mice (db/db), a mouse model of diabetes. The function of miR291b-3p is unknown. The potential role of miR-291b-3p in regulating hepatic lipid metabolism was explored in this study. High-fat diet (HFD)-and chow-fed mice were injected with an adenovirus expressing a miR-291b-3p inhibitor and a miR291b-3p mimic through the tail vein. Hepatic lipids and lipogenic gene expression were analyzed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 51 publications
7
32
0
Order By: Relevance
“…In our previously study, we identified AMPK as a primary target of miR-291, and revealed that miR-291 inhibitors ameliorated hepatic TG accumulation, reduced FAS and SREBP-1 activity and this was attributed to the targeting of miR-291b-3p of AMPK24. In the present study, we found that short-term fasting led to increased level of miR-291b-3p (Fig.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In our previously study, we identified AMPK as a primary target of miR-291, and revealed that miR-291 inhibitors ameliorated hepatic TG accumulation, reduced FAS and SREBP-1 activity and this was attributed to the targeting of miR-291b-3p of AMPK24. In the present study, we found that short-term fasting led to increased level of miR-291b-3p (Fig.…”
Section: Resultssupporting
confidence: 68%
“…We previously identified that the hepatic levels of miR-291b-3p were decreased by ~40%, accompanied by a significant reduction in the liver weight and the liver weight-to-body weight ratio, and a significant decrease in hepatic lipid deposition24. In the present study, compared with ad-GFP-treated mice (ad-NC), the HFD-fed mice injected with ad-miR-291i exhibited a significant reduction in fasting blood glucose levels.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Abnormal expression of miRNAs has been widely identified in different physiological and pathological circumstances [12][13][14]. For instance, miR-291b-3p was recently found to prompt hepatic lipogenesis mainly by targeting AMPKα1, and miR-125b enhances lipogenesis through binding the 3'UTR of SCD-1 [12,13]. In the current study, we mainly focus on miR-155, which has been widely explored in tumors [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Through a base-pairing mechanism, the mature miRNAs can bind to the 3′-untranslated region (UTR) of their target mRNAs, resulting in mRNA degradation [11]. Abnormal expression of miRNAs has been widely identified in different physiological and pathological circumstances [12][13][14]. For instance, miR-291b-3p was recently found to prompt hepatic lipogenesis mainly by targeting AMPKα1, and miR-125b enhances lipogenesis through binding the 3'UTR of SCD-1 [12,13].…”
Section: Introductionmentioning
confidence: 99%